Concentration Effects of Platelets, Fibrinogen and Thrombin on Platelet Aggregation and Fibrin Clotting - Chao, Francis C.; Tullis, James L.; Kenney, Dianne M.; Conneely, Gail S.; Doyle, John R. (Thrombosis and Haemostasis, 1974)
The effects of varying concentrations of platelets, fibrinogen and thrombin on platelet aggregation and on fibrin clotting were investigated. The results indicated that a threshold thrombin to platelet concentration ratio may be required to cause platelet activation. Above the threshold ratio, platelets exhibited properties which enhanced thrombin action in causing aggregation and fibrin clotting. At T/P ratios below the threshold level, the presence of platelets reduced thrombin activity, in other words, platelets exerted an antithrombin action. Fibrinogen at low concentrations (0.02-1.5 mg/ml) enhanced platelet aggregation induced by thrombin; whereas, at high concentrations of fibrinogen (2.0-4.0 mg/ml), aggregation was markedly inhibited. Continuous mixing of samples of platelets and fibrinogen at physiological concentrations with thrombin at low concentrations ( ˂ 2.0 U/ml) resulted in platelet aggregation. On the other hand, fibrin clots formed in samples without mixing or with high thrombin concentrations (≥ 5.0 U/ml). These results suggested that the quantitative relationships between platelets, fibrinogen and thrombin, and the presence or absence of cell contact may be important factors in determining the overall hemostasis.